Green fluorometric strategy for simultaneous determination of the antihypertensive drug telmisartan (A tentative therapeutic for COVID-19) with Nebivolol in human plasma - Mohamed M. Salim; Aya saad Radwan; Ghada M. Hadad; Fathalla Belal; Mahmoud M. Elkhoudary (Scientific Reports, 2023)
Abstract Telmisartan (TEL) and Nebivolol (NEB) are frequently co-formulated in a single dosage form that is frequently prescribed for the treatment of hypertension, moreover, telmisartan is currently proposed to be used to treat COVID19-induced lung inflammation. Green rapid, simple, and sensitive synchronous spectrofluorimetric techniques for simultaneous estimation of TEL and NEB in their co-formulated pharmaceutical preparations and human plasma were developed and validated. Synchronous fluorescence intensity at 335 nm was used for TEL determination (Method I). For the mixture, the first derivative synchronous peak amplitudes (D1) at 296.3 and 320.5 nm were used for simultaneous estimation of NEB and TEL, respectively (Method II). The calibration plots were rectilinear over the concentration ranges of 30–550 ng/mL, and 50–800 ng/mL for NEB and TEL, respectively. The high sensitivity of the developed methods allowed for their analysis in human plasma samples. NEB`s Quantum yield was estimated by applying the single-point method. The greenness of the proposed approaches was evaluated using the Eco-scale, National Environmental Method Index (NEMI), and Green Analytical Procedure Index (GAPI) methods.